Assessment of reproductive biology of Garra langlungensis (Teleostei: Cyprinidae) from the Langlung River, Nagaland, India - Sophiya Ezung; Pranay Punj Pankaj (Journal of Fisheries)
The stone sucker, Garra langlungensis Ezung, Shaingningam & Pankaj, 2021, is confined to the Langlung River, near Zutovi village in Dimapur district of Nagaland, India. This endemic fish is a common food item among the local people. There is scarce information available on this species. Despite its rising exploitation, the lack of data could contribute to its decline and potential loss. The present study involved analysis of 213 specimens from the Langlung River, collected monthly over a period of one year, to determine the sex ratio, gonadosomatic Index (GSI), and fecundity. The sex ratio of males to females was 1:0.43 (deviation from the expected 1:1 ratio), showing a male-dominated population. The monthly assessment of GSI indicated that G. langlungensis breed once a year, with maximum GSI values of 8.1 (male) and 11.5 (female) in April and a short breeding season extending from February to May. Fecundity, based on data from 16 mature fish specimens, was the highest (844 eggs) in 77.9 mm TL (0.56 g) and the lowest (319 eggs) in 55.2 mm TL specimen (0.23 g). A significant correlation between fecundity and ovary weight (r = 0.915) was recorded. This study provides insights into the sex ratio, GSI, and fecundity of G. langlungensis, which facilitate the identification of fish stocks in their natural habitats and the development of appropriate conservation measures.